URGENCY OF PHILOSOPHICAL THINKING IN GUIDANCE AND COUNSELING PRACTICE: A LITERATURE REVIEW - Maulida, Salma Nur (OPTIMA: Journal Of Guidance and Counseling, 2025)
Guidance and counseling is a crucial component of the national education system that supports the achievement of educational goals. Philosophy plays a key role in shaping the scientific foundation and principles underlying the practice of guidance and counseling. This study aims to explore the role of philosophy in the development of guidance and counseling theory and practice, focusing on the contributions of ontology, epistemology, and axiology in enriching counselors' understanding of human nature, wise decision-making, and the application of ethical values in professional practice. Additionally, this study examines the relevance of Pancasila philosophy as the Indonesian philosophical system in shaping guidance and counseling services that align with the cultural and social values of Indonesian society.The method used in this research is a systematic literature review (Systematic Literature Review), aimed at collecting, evaluating, and analyzing findings from various studies related to the topic. This research involves gathering articles related to the philosophy of science in guidance and counseling and analyzing them to find insights that can enrich the practice of guidance and counseling in Indonesia. The results of the study indicate that philosophy plays a very important role in guiding the development and application of guidance and counseling, both in the context of multicultural societies and the digital era. Philosophy provides a foundational framework that helps counselors understand human characteristics, professional values, and the social and technological challenges faced in counseling practice. Particularly in the context of Indonesia, the application of Pancasila philosophy as a national philosophical framework offers a more relevant and contextually appropriate approach that ensures guidance and counseling services remain of high quality, relevant, and sustainable. This study affirms that understanding philosophy is not just an addition but an essential element in the sustainability and quality of guidance and counseling services.